Inferring the HII region escape fraction of ionizing photons from infrared emission lines in metal-poor star-forming dwarf galaxies - Ramambason, Lise; Lebouteiller, V.; Bik, A.; Richardson, C. T.; Galliano, F.; Schaerer, D.; Morisset, C.; Polles, F. L.; Madden, S. C.; Chevance, Mélanie; Looze, I. De (Astronomy and astrophysics, 2022)
Local metal-poor galaxies stand as ideal laboratories for probing the properties of the interstellar medium (ISM) in chemically unevolved conditions. Detailed studies of this primitive ISM can help gain insights into the physics of the first primordial galaxies that may be responsible for the reionization. Quantifying the ISM porosity to ionizing photons in nearby galaxies may improve our understanding of the mechanisms leading to Lyman continuum photon leakage from galaxies. The wealth of infrared (IR) tracers available in local galaxies and arising from different ISM phases allows us to constrain complex models in order to estimate physical quantities.